Wasathiyah Quality Management: A Approach in Islamic Education Quality Management - Thoriq Aziz Jayana; Dadang Ahmad Sujatnika; Zainuddin Syarif; Wahyudin Noor (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2022)
This paper explores the wasathiyah approach to quality management in Islamic educational institutions. The research uses library research methods to build an established scientific discourse. The study results show that in the management of Islamic educational institutions, which includes input, process, and output, it is necessary to apply the Wasathiyah approach. The implication of this research is to provide the principle of balance in managing the quality of Islamic education following the values in wasathiyah so that educational institutions can remain grounded in the values of balance (wasath). Currently, the secularization of Islamic educational institutions has led to the loss of the goals of Islamic education. Therefore, the Wasathiyah approach to managing education can maintain the institution's balance.